The chemical properties of acid soils with emphasis on soils of the humid tropics - Gillman, G.P. (1991)
This paper does not present an exhaustive review of the properties of acid soils. Rather, emphasis is placed on three topics, viz. soil pH, exchange properties, and sulfate sorption, with bias towards the author’s experience with soils from the world humid tropical region. The discussion on pH and exchange properties centers around the selection of laboratory methods, which should give relevant information about field conditions, and about the application of this knowledge to soil management. Sulfate sorption mechanisms for variable and constant charge minerals are distinguished, and the likely role of exchangeable Al is discussed. There are no abrupt changes in soil properties at the 23° parallel, so that the principles discussed should generally be applicable to a wide variety of acid soils throughout the world.